Regulation of Pear Fruit Quality: A Review Based on Chinese Pear Varieties - Ying Zhang; Yudou Cheng; Yuru Ma; Junfeng Guan; Hao Zhang (Agronomy)
Fruit quality is one of the most important economic traits of fruit crops, directly influencing market prices and orchard revenues. Enhancing fruit quality has therefore become a critical objective in both fruit production and scientific research. External quality traits of fruits typically include size, coloration, shape, uniformity, and consistency. Internal quality traits refer to the nutritional value of fruits, which largely determine their flavor and palatability. Over the past decade, significant progress has been made in understanding the formation and regulatory mechanisms of fruit quality, with numerous key functional genes associated with quality traits being identified. While substantial advancements have been achieved in studying specific aspects of fruit quality, there remains a lack of comprehensive and systematic reviews addressing the overall physiology of fruit quality, the interplay among various quality traits, and the diversity of regulatory mechanisms. Using Chinese pears as an example, this review summarizes the research progress in fruit quality regulation over the past five years. Key aspects include metabolic regulation of fruit traits such as sweetness, color, texture, and physiological disorders; factors influencing stone cell formation; sugar content regulation; roles of plant hormones including ethylene, gibberellins, and abscisic acid; translational regulation and post-translational modifications such as ubiquitination, methylation, and acetylation; as well as the application of genomic sequencing technologies. Furthermore, the review offers practical suggestions for improving pear fruit quality and provides insights for researchers in related fields. Finally, future trends in fruit quality research are discussed, offering a forward-looking perspective for advancing the field.